2014
DOI: 10.15252/embr.201438932
|View full text |Cite
|
Sign up to set email alerts
|

Hrr25 kinase promotes selective autophagy by phosphorylating the cargo receptor A tg19

Abstract: Autophagy is the major pathway for the delivery of cytoplasmic material to the vacuole or lysosome. Selective autophagy is mediated by cargo receptors, which link the cargo to the scaffold protein Atg11 and to Atg8 family proteins on the forming autophagosomal membrane. We show that the essential kinase Hrr25 activates the cargo receptor Atg19 by phosphorylation, which is required to link cargo to the Atg11 scaffold, allowing selective autophagy to proceed. We also find that the Atg34 cargo receptor is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 36 publications
7
97
0
Order By: Relevance
“…In parallel with this study, we found that Hrr25 also phosphorylates Ser391 of Atg19, which corresponds to Ser383 of Atg34, to enhance the Atg19-Atg11 interaction, resulting in the stimulation of the Cvt pathway [17]. Similar results were also reported by another group [27]. In addition, we showed that Atg36, a receptor for autophagic degradation of peroxisomes (pexophagy) [30,31], is also phosphorylated by Hrr25 to interact with the common adaptor Atg11 [17].…”
Section: Hrr25 Promotes Atg11 Targeting To the Ams1 Complex By Enhancsupporting
confidence: 90%
See 1 more Smart Citation
“…In parallel with this study, we found that Hrr25 also phosphorylates Ser391 of Atg19, which corresponds to Ser383 of Atg34, to enhance the Atg19-Atg11 interaction, resulting in the stimulation of the Cvt pathway [17]. Similar results were also reported by another group [27]. In addition, we showed that Atg36, a receptor for autophagic degradation of peroxisomes (pexophagy) [30,31], is also phosphorylated by Hrr25 to interact with the common adaptor Atg11 [17].…”
Section: Hrr25 Promotes Atg11 Targeting To the Ams1 Complex By Enhancsupporting
confidence: 90%
“…A recent study identified two phosphorylated residues (Ser382 and Ser383) in the Atg11-binding region of Atg34 by mass spectrometry, and also reported that the simultaneous Ala replacement of these residues abolished autophagic transport of Ams1 [27]. In this study, we showed that the S383A mutation but not the S382A mutation impaired Atg34 transport to the vacuole (Fig.…”
Section: Hrr25 Promotes Atg11 Targeting To the Ams1 Complex By Enhancsupporting
confidence: 67%
“…Several of the Atg proteins are phosphorylated, but until recently it was not known if any of these proteins were Atg1 substrates. Many other protein kinases (i.e., proteins that are not part of the autophagy core machinery) also modulate autophagy activity, [25][26][27][28] but in most cases the relevant targets have not been identified. Atg9 plays a key role in autophagy, and we recently demonstrated that the amount of the Atg9 protein correlates with the rate of autophagosome formation.…”
Section: Determination Of Atg9 Phosphorylation Sitesmentioning
confidence: 99%
“…For example, phosphorylation of Atg19 by Hrr25 and of Atg32 by casein kinase 2 is required for their interaction with Atg11. 73,74 Phosphorylation plays dual roles in regulating the scaffolding and kinase functions of ULK1 to coordinate the autophagic response in mammalian cells. 75 In human embryonic kidney (HEK)-293 cells, autophosphorylation at Thr180 within the ULK1 kinase-activation loop is required for sustaining ULK1 kinase activity and its intracellular localization to phagophores upon starvation.…”
mentioning
confidence: 99%